2008
DOI: 10.1063/1.2831222
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mechanical boundary conditions on the electrocaloric properties of ferroelectric thin films

Abstract: A thermodynamic analysis of the electrocaloric ͑EC͒ effect in BaTiO 3 ferroelectric thin films has been carried out under differing mechanical boundary conditions. It is shown that both the magnitude of the electrocaloric effect and temperature at which it is maximized depend not only on the extent of the applied field change but also on the value of the initial field. For initial fields smaller than a critical value the EC effect is largest at the phase transition temperature but the effect is a strong functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
119
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(125 citation statements)
references
References 22 publications
5
119
0
1
Order By: Relevance
“…12 Moreover, changing the mechanical boundary conditions by varying the epitaxial misfit strain can remarkably affect the phase transition, which may be helpful to tune the elastocaloric properties of ferroelectric thin films. [16][17][18][19] This is of great interest and importance to design the elastocaloric cooling devices in the future and therefore motivates us to study the elastocaloric effect in ferroelectric thin films under the influence of epitaxial strain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 Moreover, changing the mechanical boundary conditions by varying the epitaxial misfit strain can remarkably affect the phase transition, which may be helpful to tune the elastocaloric properties of ferroelectric thin films. [16][17][18][19] This is of great interest and importance to design the elastocaloric cooling devices in the future and therefore motivates us to study the elastocaloric effect in ferroelectric thin films under the influence of epitaxial strain.…”
mentioning
confidence: 99%
“…[36][37][38][39] In particular, the electrocaloric properties of BTO thin films have been intensively investigated. 12,18,19,26,[40][41][42][43][44][45][46][47] Interestingly, it was reported that applying a uniaxial compressive stress could enhance and widen the electrocaloric response considerably in ultrathin BTO films due to tuning of the depolarization field. 26 It is also reported that the electrocaloric peak under tensile stresses moves towards higher temperatures with its magnitude slightly enhanced in BTO single crystals.…”
mentioning
confidence: 99%
“…If the direction of E remains fixed during the poling, polarisation azimuthal angle θ stays constant, while only the amplitude P 0 changes value. Such amplitudon mode of polarisation switching is usually seen in conventional EC materials, 5,6,34,35 where the largest variations in P 0 and thus the largest changes in p γ and ΔT occur near T C .…”
Section: Introductionmentioning
confidence: 99%
“…For the poling field ΔE γ $ 200 kV=cm, we obtain the values of ΔT in the range of 1-2 K (Supplementary Figure 2), which is similar to the performance of conventional EC materials undergoing amplitudon-polarisation switching. 5,6,34,35 In the case of low-field poling, i.e., for E γ;a $ 1 -5 kV=cm and ΔE γ 10-30 kV=cm, the sombrero-hat energy landscape is only slightly perturbed. If the P99 [100] state of Figures 1b and c is taken as a starting point, applying noncollinear E induces a rotation of the polar vector along the minimum-energy groove until P99E.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation